2020
DOI: 10.1111/odi.13340
|View full text |Cite
|
Sign up to set email alerts
|

Submandibular gland excision: From external surgery to robotic intraoral and extraoral approaches

Abstract: Submandibular gland excision is generally performed through a transcervical approach, a safe procedure that, however, carries few neurological, functional and aesthetic drawbacks. Intraoral approach to the submandibular gland has been described many years ago but it has been newly proposed in recent years thanks to endoscope‐assisted and robot‐assisted surgical procedures. The main purpose of intraoral approaches is to avoid cosmetic sequelae and to reduce the risk of marginal nerve injury although the recent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
(49 reference statements)
0
7
0
Order By: Relevance
“…[1,6,26] Traditional cervical incision approaches similar to selective neck dissection created non-negligible concerns about postoperative esthetics. Minimally-invasive robotic neck surgery via hidden incision approaches then emerged, and the incisions could be categorized into 3 different groups: retroauricular hairline incisions (RAHIs), [15,27,28] modified facelift incisions, [29,30] and transhairline incisions, [13,[31][32][33] as shown in Fig. 2C.…”
Section: Discussionmentioning
confidence: 99%
“…[1,6,26] Traditional cervical incision approaches similar to selective neck dissection created non-negligible concerns about postoperative esthetics. Minimally-invasive robotic neck surgery via hidden incision approaches then emerged, and the incisions could be categorized into 3 different groups: retroauricular hairline incisions (RAHIs), [15,27,28] modified facelift incisions, [29,30] and transhairline incisions, [13,[31][32][33] as shown in Fig. 2C.…”
Section: Discussionmentioning
confidence: 99%
“…The magnification and dexterity provided by the robotic surgical system allow precise dissection and preservation of the lingual nerve, hypoglossal nerve, and Wharton’s duct. According to Cammaroto et al, the TORS approach is recommended due to its improved hemostatic control of the facial artery, which can be difficult to manage in an intraoral open approach [ 73 ].…”
Section: Reviewmentioning
confidence: 99%
“…us, dental endoscopy has also been reported for implant surgery [22]. Historical studies have shown that endoscopy can assist periodontal surgery [23], joint surgery [24], bone marrow cavity observation [25], wound repair [26,27], osteotomy [28], salivary lithotripsy [29,30], biopsy [31,32], polypectomy [33], stereotactic radiotherapy [34], tumor removal [35], and even nerve visualization [36]. It also has certain significance for oral distance teaching and telediagnosis [37].…”
Section: Dental Endoscopesmentioning
confidence: 99%